Wireless Sensor Network transport protocol: A critical review - Rathnayaka, Dinusha; Potdar, Vidyasagar (Academic Press, 2011)
The transport protocols for Wireless Sensor Network (WSN) play vital role in achieving the high performance together with longevity of the network. The researchers are continuously contributing in developing new transport layer protocols based on different principles and architectures enabling different combinations of technical features. The uniqueness of each new protocol more or less lies in these functional features, which can be commonly classified based on their proficiencies in fulfilling congestion control, reliability support, and prioritization. The performance of these protocols has been evaluated using dissimilar set of experimental/simulation parameters, thus there is no well defined benchmark for experimental/simulation settings. The researchers working in this area have to compare the performance of the new protocol with the existing protocols to prove that new protocol is better. However, one of the major challenges faced by the researchers is investigating the performance of all the existing protocols, which have been tested in different simulation environments. This leads the significance of having a well-defined benchmark for the experimental/simulation settings. If the future researchers simulate their protocols according to a standard set of simulation/experimental settings, the performance of those protocols can be directly compared with each other just using the published simulation results.This article offers a twofold contribution to support researchers working in the area of WSN transport protocol design. First, we extensively review the technical features of existing transport protocols and suggest a generic framework for a WSN transport protocol, which offers a strong groundwork for the new researchers to identify the open research issues. Second we analyse the experimental settings, focused application areas and the addressed performance criteria of existing protocols; thus suggest a benchmark of experimental/simulation settings for evaluating prospective transport protocols.